Community, time, and the art of self-destruction in the books of Jack Spicer. - Clarkson, Ross. (University of Ottawa (Canada), 2001)
Jack Spicer's life and work was intimately bound up with a sense of community. His poetry workshop in 1957, his poetic companionship with Robin Blaser and Robert Duncan, and his involvement with young poets in the Bay Area, all point to a conception of poetry as community. It is, however, his relationship to past poets and the "tradition" of modern poetry that this thesis mainly focuses on. From the beginning to the end of my thesis, the problematic meaning of this tradition is explored. My thesis is that Spicer's poetry does not create a vision, or conception of community, but creates an instance of community. Time figures into Spicer's sense of community because it is by bringing the past to bear on the present that communities survive into the future, but also because an "experience of time" is shared and passed on by his poetry. This experience of time is, however, problematic for the self and its sense of identity. Time undermines the self-sameness of identity, and thus an art that exposes the self to time would be an "art of self-destruction." In a sense, the poet outlives his/her identity. The art of self-destruction, as I conceive it, is an art of survival, not an ode to suicide.
Keywords: Literature, American.